The Personal in the Collective: Rethinking the Secular Subject in Relation to the Military, Wifehood, and Islam in Turkey - Dagtas, Mahiye Secil (Feminist studies, 2016)
Drawing on research with Turkish military wives between 2006-2009, this article aims to address the gendered dynamics of secular subject formation in Turkey beyond the powerful antagonism between political Islam and secularism. Although the distinction is constantly being complicated by the acts and words of women who reside at the peripheries of official discourses even in their embracement of state ideologies, it continues to haunt contemporary debates and scholarship on Turkey and the Middle East. In this article, I focus on the narratives of women who are conjugally and emotionally attached to the Turkish military, an institution that has historically been seen as the founder and guardian of Turkish secularism against religious forces. I take these narratives as secular modes of representation and self-representation reflective of a range of ethical, social, and material dispositions. I argue that while the life-stories of these women reveal secularism’s institutional investments in the female body, they also convey a sense of agency and subjectivity enabled by such investments. As such, they highlight the need to apprehend the secular via its sensorial and affective dimensions and not only its political and institutional manifestations as well as the need to recognize the gendered nature of these dimensions.